Cu2XSnS4 (X = Mn, Fe, Co) semiconductors: Boltzmann theory and DFT investigations. (November 2021) - Nouri, Youssef; Hartiti, Bouchaib; Batan, Abdelkrim; Labrim, Hicham; Fadili, Salah; Thévenin, Philippe
Abstract: Cu2 XSnS4 (X = Mn, Fe, Co) semiconductor represent one of the most promising quaternary family for the photovoltaic devices. For this purpose, a comparative study of structural, electronic, linear/non-linear optical and thermoelectrical properties of Cu2 XSnS4 based on the first-principles calculations and Boltzmann theory was done, using the generalized gradient approximation GGA with applying the Hubbard on-site coulombic correction to Mn, Fe and Co cations. The computation of the lattice constants shows a good agreement with the experimental results, also the simulation of X-ray diffraction (XRD) spectra shows that the compounds have crystallized in the polycrystalline kesterite form with a preferential orientation along (112) plane. The GGA + U method offering that CMTS, CFTS and CCTS materials exhibit a duality ferromagnetic semiconductor behavior. The optical properties showed good optical absorption in order of 20 and 30 (10 4 cm −1 ) for the three compounds, and a high optical conductivity in the visible range. Thus, the non-linear optical properties as well as suitable optical band gaps of about 1.44–1.56 eV confirms the applicability of CMTS, CFTS and CCTS materials as absorbent layers in photovoltaic solar cells. In addition, the thermoelectric properties such as electrical conductivity ( σ / τ ), Seebeck coefficient ( S ) and power factor ( S 2 σ / τ ) as a function of temperature were investigated using Boltztrap package, we have found that CMTS, CFTS and CCTS kesterite materials exhibit p-type behavior and good thermoelectric transport properties in the temperature range of 300 - 800 K, therefore, we expect these materials to be potential candidates for clean energy applications. Highlights: The electronic properties shown that Cu2XSnS4 (X = Mn, Fe, Co) materials have a duality ferromagnetic semiconductor, direct and quasi-direct band gap character. The linear and nonlinear optical properties show that the Cu2XSnS4 (X = Mn, Fe, Co) an excellence materials for photonic and photovoltaic applications. The thermoelectrical properties show that the Cu2XSnS4 (X = Mn, Fe, Co) materials to be potential candidates for clean energy applications.